2020
DOI: 10.3390/molecules25245918
|View full text |Cite
|
Sign up to set email alerts
|

Tetrabutylammonium Bromide (TBAB) Catalyzed Synthesis of Bioactive Heterocycles

Abstract: During the last two decades, tetrabutylammonium bromide (TBAB) has gained significant attention as an efficient metal-free homogeneous phase-transfer catalyst. A catalytic amount of TBAB is sufficient to catalyze various alkylation, oxidation, reduction, and esterification processes. It is also employed as an efficient co-catalyst for numerous coupling reactions. It has also acted as an efficient zwitterionic solvent in many organic transformations under molten conditions. In this review, we have summarized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 121 publications
0
31
0
2
Order By: Relevance
“…Reaksi antara ion fenoksida dengan dimetilsulfat mengikuti sintesis eter Williamson, yaitu substitusi nukleofilik bimolekular (SN 2 ). Sintesis eter aromatis melalui pembentukan ion fenoksida dapat juga diperoleh dengan menggunakan kondisi basa KOH dengan katalis fase transfer tetra butil ammonium bromide untuk senyawa fenol yang tidak larut air mengikuti mekanisme reaksi SN 2 [13,14].…”
Section: Hasil Dan Diskusiunclassified
See 1 more Smart Citation
“…Reaksi antara ion fenoksida dengan dimetilsulfat mengikuti sintesis eter Williamson, yaitu substitusi nukleofilik bimolekular (SN 2 ). Sintesis eter aromatis melalui pembentukan ion fenoksida dapat juga diperoleh dengan menggunakan kondisi basa KOH dengan katalis fase transfer tetra butil ammonium bromide untuk senyawa fenol yang tidak larut air mengikuti mekanisme reaksi SN 2 [13,14].…”
Section: Hasil Dan Diskusiunclassified
“…Perbedaan bentuk antara material awal dan hasil sintesis dapat dikarenakan oleh adanya perubahan struktur berupa terjadinya metilasi pada gugus -OH karboksilat dan -OH fenolik. Senyawa AOHS memiliki dua gugus -OH yang memungkinkan terjadi gaya antar molekul yang lebih kuat berupa ikatan hidrogen, seperti yang terjadi pada senyawa golongan asam karboksilat maupun fenol [14]. Ikatan hidrogen itu tidak tampak lagi saat dilakukan metilasi untuk menggantikan kedua gugus -OH tersebut, sehingga membuat senyawa MOMS memiliki ikatan molekul yang lebih lemah yaitu gaya Van der walls dan mengakibatkan perubahan bentuk senyawa menjadi cair.…”
Section: Hasil Dan Diskusiunclassified
“…To solve the problem of harsh conditions in HDS, the relatively expensive raw materials of ILs and the loss of H 2 O 2 in catalytic oxidative desulfurization, TBAB and PEG-200 were selected as the raw materials of a DES according to previous studies. Both TBAB and TBAC can also be used as phase transfer catalysts and ion pair reagents, [38][39][40][41] but the cost of TBAB is lower than that of its counterpart. Hence, TBAB/PEG-200 DESs with different molar ratios were synthesized by using PEG-200 as the HBD and TBAB as the HBA and characterized by Fourier transform infrared (FT-IR) spectroscopy and 1 H nuclear magnetic resonance ( 1 H NMR) spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Heterocyclic skeletons are very common in naturally occurring bioactive compounds as well as in commercially available drug molecules [1][2][3]. Spiro-oxindoles and 4-hydroxycoumarin both moieties are very common in naturally occurring bioactive compounds [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Crystal structure was determined by using single X-ray crystallography technique. It was found that the crystals are triclinic with space group P-1, C108H60Br4N4O29S2: a = 11.8333(6) Å, b = 12.8151(6) Å, c = 17.1798(8) Å, α = 77.317(4)°, β = 74.147(4)°, γ = 66.493(5)°, V = 2280.0(2) Å 3 , Z = 1, T = 149.99(10) K, μ(MoKα) = 1.902 mm -1 , Dcalc = 1.647 g/cm 3 , 11545 reflections measured (3.836° ≤ 2Θ ≤ 50.998°), 8310 unique (Rint = 0.0488, Rsigma = 0.0875) which were used in all calculations. The final R1 was 0.0622 (I > 2σ(I)) and wR2 was 0.1994 (all data).…”
mentioning
confidence: 99%